Marketing Mix Analysis of Purchasing Decisions and Consumer Satisfaction of Palm Harvesting Equipment at PT. Carosteel Media Panen - Cyntia Tiodora Silalahi; Alvi Furwanti Alwie; Raden Lestari Garnasih (Indonesian Journal of Economics, Social, and Humanities, 2026)
This study aims to analyze the effect of product, price, location, and promotion on purchasing decisions and customer satisfaction at PT Carosteel Media Panen. This study uses a quantitative approach with a descriptive research design to assess the impact of the marketing mix on purchasing decisions and consumer satisfaction regarding oil palm harvesting tools at PT Carosteel Media Panen. The study was conducted in Pekanbaru starting in February 2024, with data collected through online questionnaires distributed to 45 client companies of PT Carosteel Media Panen. The data used consisted of primary data obtained directly from respondents and secondary data from other sources. Data analysis techniques include validity and reliability tests to ensure the quality of the instrument, as well as descriptive analysis to describe the data. Statistical analysis was conducted using structural equation modeling (SEM) to test the relationship between variables and measure the goodness-of-fit of the model. The hypothesis will be accepted if the significance value is below 0.05, which indicates a significant relationship between variables. The study results reveal that product, price, location, promotion, and purchasing decisions together have a significant influence on customer satisfaction, which in turn has an impact on purchasing decisions at PT. Carosteel Media Harvest.